An Analytical Study of Corporate Social Responsibility Spending by Companies Based on Government of India's CSR Mandate - Ramesh, G.; Peswani, Shilpa (Prabandhan: Indian Journal of Management, 2017)
Over the years, the concept of corporate social responsibility (CSR) has gained wider implications not only from a philanthropic perspective, but also from a real business standpoint. This paper attempted to identify how large and successful companies in India have contributed towards CSR activities on the basis of norms and regulations prescribed by the Indian authorities as stipulated in the Company's Act, 2013. This paper also attempted to categorize the companies based on the degree of conducting various CSR activities as mandated by the Companies Act. We have provided the findings and recommendations on the basis of descriptive and inferential analysis. This paper also attempted to deliver some guidance to those companies who are yet to start their CSR activities or have contributed very little on the CSR front.